Ten lectures on cognitive linguistics and the unification of spoken and signed languages - Wilcox, Sherman (Distinguished Lectures in Cognitive Linguistics Ser., 2017)
In Ten Lectures on Cognitive Linguistics and the Unification of Spoken and Signed Languages Sherman Wilcox suggests that rather than abstracting away from the material substance of language, linguists can discover the deep connections between signed and spoken languages by taking an embodied view. This embodied solution reveals the patterns and principles that unite languages across modalities. Using a multidisciplinary approach, Wilcox explores such issues as the how to apply cognitive grammar to the study of signed languages, the pervasive conceptual iconicity present throughout the lexicon and grammar of signed languages, the relation of language and gesture, the grammaticization of signs, the significance of motion for understanding language as a dynamic system, and the integration of cognitive neuroscience and cognitive linguistics.